Jamkesmas Health Service Fee Waiver - World Bank (World Bank, Jakarta, 2017)
Macroeconomic growth and incomes have been on the rise since the Asian Financial Crisis (AFC), but health service utilization and health outcomes in Indonesia have been slower to improve. Jamkesmas could provide valuable benefits by allowing cardholders to acquire preventative, curative, and catastrophic health care services without fees. When it promotes healthy households, keeps students active, alert, and participating in their education, returns adults to work sooner, and saves households from the high costs of healthcare, Jamkesmas' sizeable individual benefits should be matched by increased social benefits resulting from a healthy and productive population. Jamkesmas has been provided to poor households, but many non-poor have also received Jamkesmas benefits due to dual central and local targeting processes which have led to frequent mismatches and errors in coverage. Health service providers find Jamkesmas difficult and costly to implement resulting in fewer services provided, and funds spent, on Jamkesmas beneficiaries. Local regulations regarding public health center management often conflict with Jamkesmas mandates, leaving health service providers confused and unwilling to use Jamkesmas funds to provide Jamkesmas beneficiaries with planned services. The future costs of an improved Jamkesmas program have not been adequately publicized and Jamkesmas' financial, fiscal, and political sustainability is uncertain.